Linguistic and cultural difficulties in Arabic-English translation of sentences among Saudi undergraduates - Jabak, Omar Osman (2018)
There have been very few studies on the linguistic and cultural difficulties in Arabic-English translation encountered by Arab undergraduate students to date. The present study aims to explore the linguistic and cultural difficulties experienced by 50 Saudi undergraduate students when they translate Arabic sentences into English and the underlying reasons behind these difficulties along with the solutions to these difficulties. This study uses a qualitative approach and two data collection tools which are evaluation instruments and semi-structured interviews. It also uses Newmark’s (1998, 2011) and Dickins’et al (2017) theoretical views on translation from one’s mother tongue into a foreign language as its theoretical framework. The analysis of the data revealed eleven linguistic difficulties, reasons behind the linguistic difficulties, ways of overcoming these linguistic difficulties, three main cultural difficulties with ten subcategories and reasons for these cultural difficulties and ways of overcoming the cultural difficulties, which all represent the findings of the study. Some of the linguistic difficulties encountered by the Saudi undergraduate students include indirect questions, articles, direct questions, conditional sentences, interjections, prepositions and relative pronouns. Some of the underlying reasons for such difficulties are the students’ adherence to literal translation, the differences in the linguistic systems of Arabic and English, and the application of Arabic grammar rules to English translation. The cultural difficulties are idioms, collocations and proverbs with their respective subcategories. Some of the reasons for these difficulties are the students’ commitment to literal translation, the students’ lack of the cultural knowledge of both Arabic and English, the students’ heavy reliance on bilingual dictionaries, lack of bilingual specialized dictionaries on these cultural aspects of both Arabic and English and lack of Arabic-English translation practice as compared to English-Arabic translation. It is hoped that this study, along with its findings and suggestions, will contribute to improving Saudi undergraduate students’ quality of Arabic-English translation and provide new insights into the difficulties of Arabic-English translation as well as the difficulties of carrying out translation from the mother tongue into a foreign language.